Pengaruh Imbalan Bagi Hasil dan Suku Bunga Bank Indonesia Terhadap Pertumbuhan Deposito Mudharabah - Anam, Hairul (Research Institution and Community Service Wijaya Kusuma Surabaya University, 2014)
The Influence of Profit Sharing and Interest Rates of Bank Indonesia on The Growth of Mudharabah Deposits; This study aimed to examine the effect of profit sharing and interest rates of Bank Indonesia on the growth of mudharabah deposits at PT. Bank Muamalat Indonesia, Tbk. The method used in this study was the quantitative research in methods of data collection techniques of documentation. Sample consists of 35 sample from the quarterly report of PT Bank Muamalat Indonesia, Tbk from January 2005 to September 2013. The method used is the multiple linear regression method. Based on this analysis of the obtained research results showed that profit sharing and interest rates of Bank Indonesia simultaneously influence significantly to growth of mudharabah deposits in Bank Muamalat Indonesia. This shows that information about profit sharing and interest rates of Bank Indonesia can be used to predict the growth of mudharabah deposits in Bank Muamalat Indonesia and collectively can make policy in investment decision making. And other results obtained that profit sharing and interest rates of Bank Indonesia partially positive and significant effect on the growth of deposits mudharabah in Bank Muamalat Indonesia. Results of this study are consistent with previous research indicated by Sutiani (2012) that profit sharing the positive effect of the nominal amount of the savings account holders in the Islamic bank. Because its customers are only willing to keep their funds in the bank that is willing and able to pay back these funds when billed. This proves that the majority of Indonesia's muslim community is still affected by the return will be accepted. The implications of this study are expected in management can improve the performance and management can work together with the Indonesian Ulema council to provide wider dissemination of the prohibition of bank interest is expected to enhance the bank's syariah.